Oxygen isotopic evidence for high‐magnitude, abrupt climatic events during the Lateglacial Interstadial in north‐west Europe: analysis of a lacustrine sequence from the site of Tirinie, Scottish Highlands. (18th July 2016) - Candy, I.; Abrook, A.; Elliot, F.; Lincoln, P.; Matthews, I. P.; Palmer, A.
ABSTRACT: The Last Glacial to Interglacial Transition (LGIT) is a period of climatic instability. δ 18 O records are ideal for investigating the LGIT as this proxy responds rapidly to even minor climatic oscillations. Lacustrine carbonates offer the opportunity to investigate spatial diversity in patterns of climatic change during the LGIT but this requires the generation of δ 18 O records from a range of latitudinal and longitudinal settings. This study presents a coupled pollen and stable isotopic study of lacustrine carbonates spanning the Windermere Interstadial (the British equivalent of Greenland Interstadial 1, the Lateglacial Interstadial) from the site of Tirinie in the Scottish Highlands, a region where δ 18 O records are absent. The Interstadial is characterized by three δ 18 O peaks, warm intervals, and two δ 18 O declines, cold episodes, the timing of which is constrained by the presence of crypto‐tephra. The landscape at Tirinie was highly responsive to these climatic oscillations as the sedimentary and pollen record respond to each isotopic shift. The paper concludes by highlighting that, across the British Isles, lacustrine δ 18 O records of the Interstadial have a consistent stratigraphy/structure, although the magnitude of the isotopic shifts is regionally variable. Potential causes of this variability are discussed.